Acute Pancreatitis Occurring after Pamidronate Infusions in Two Patients with Spondyloarthritis - Éric Toussirot; Lucine Vuitton; Stéphane Koch; Marie-Blanche Valnet-Rabier (Case Reports in Rheumatology)
We report two cases of acute pancreatitis following the administration of pamidronate given as an anti-inflammatory agent for spondyloarthritis with a recurrence in one patient when the drug was reintroduced. The upper gastrointestinal toxicity of aminobisphosphonates is well known and this drug class could be added to the list of medications that are associated with the development of pancreatitis.